OPTIMIZATION OF RECOVERY TREATMENT OF PATIENTS WITH THE UROLITHIC ILLNESS AFTER THE REMOTE LITHOTRIPSY WITH APPLICATION OF PHYTOCOMPLEXES, LASER THERAPY AND PHYSIOTHERAPY EXERCISES - I. R. Musin (Креативная хирургия и онкология)
Research  is based  on the  clinical material  including  experience of treatment of 127 patients  with an urolithic illness from  2008  for  2011. Depending on carried-out postoperative therapy patients are divided into groups  by simple way of randomization. At 44 patients of suffering urolithic illness (the  1st group), before and  after lithotripsy  complex  therapy included basic treatment with application of necessary medicines and simultaneous purpose of a  phytocomplex of original structure. At the  2nd group  (43  patients) after lithotripsy  complex therapy included basic treatment with application of necessary medicines, simultaneous purpose of a phytocomplex of original structure, laser therapy and physiotherapy exercises. Patients of the 3rd group (40 patients) received basic therapy before and after lithotripsy. The analysis of results of treatment showed that application phytocomplexes original structure in combination with procedures of laser therapy and physiotherapy exercises in postoperative rehabilitation of patients with urolithic illness promotes within a month to a full release of stones from urinary ways at 86-93% of patients in comparison with a basic complex (63%).